2016
DOI: 10.1155/2016/9652789
|View full text |Cite
|
Sign up to set email alerts
|

miR-375 and miR-205 Regulate the Invasion and Migration of Laryngeal Squamous Cell Carcinoma Synergistically via AKT-Mediated EMT

Abstract: Previous studies have found that miR-375 and miR-205 were significantly dysregulated in laryngeal squamous cell carcinoma, which contributed to the invasion and migration of LSCC. However, the mechanisms of miR-375 and miR-205 regulating the invasion and migration of LSCC remain unknown. qRT-PCR was performed in 40 pairs of tissue samples to investigate the expression of miR-375 and miR-205 in LSCC and paracarcinoma tissues. To investigate whether or not miR-375 and miR-205 regulated the invasion and migration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…First of all, the 5-year survival rate of non-small cell lung carcinoma (NSCLC) is only 11%, which means most patients can not get completely cured after their therapy [2]. Second, tumor invasion and metastasis are the major problems in disease progression and therapy failure, which cause immense cases of decease [3]. Thence, a strategy of prevention from tumor metastasis is really essential.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, the 5-year survival rate of non-small cell lung carcinoma (NSCLC) is only 11%, which means most patients can not get completely cured after their therapy [2]. Second, tumor invasion and metastasis are the major problems in disease progression and therapy failure, which cause immense cases of decease [3]. Thence, a strategy of prevention from tumor metastasis is really essential.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigating molecular biological markers, in order to analyze the invasion and migration of LSCC, is vital for improving the treatment of local invasion and cervical lymph node metastasis in patients with LSCC ( 10 , 11 ). Notably, microRNA (miRNA), such as miRNA-1 and miRNA-205, has been reported to be associated with the invasion and migration of LSCC, which contributed to the understanding of the molecular mechanism underlying the invasion and migration of LSCC ( 12 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that ERK1/2 serves arole in the process of EMT in a number of tumors ( 55 57 ). Another previous study demonstrated that miR-205 regulates invasion and migration of laryngeal squamous cell carcinoma by AKT-mediated EMT ( 58 ). In the present study, UTMD-mediated miR-205 transfection upregulated the expression of E-cadherin and downregulated MMP-9 expression, suggesting that miR-205 may inhibit EMT in PC-3 cells.…”
Section: Discussionmentioning
confidence: 96%